Energy Conservation Worksheets with Jigsaw Cooperative Learning Model to Improve Learning Outcomes Supporting SDG 4 in Science Education - Adinda Nashsrul Trihani; Ivo Yuliana (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: This research aims to produce energy conservation worksheets based on the Jigsaw type cooperative learning model that are suitable for use and effective in improving students' science learning outcomes to support SDG point 4. Method: This research is a quantitative descriptive study using the Research and Development (R&D) method, aimed at developing and testing the effectiveness of the learning product. The development process uses the ADDIE model, which includes the following stages: Analysis, Design, Development, Implementation, and Evaluation. The research population was conducted at one school with a sample of 50 students. Results: Research shows that Jigsaw-based cooperative learning worksheets are valid, practical, and effective for use in science learning on energy conservation in elementary schools. The implementation of worksheets can significantly improve student learning outcomes, as evidenced by pre-test, post-test, difference test, and N-Gain values in the experimental class. In addition, students responded positively to the learning because discussion activities and group collaboration made it more active, interesting, and easier to understand. Novelty: The innovations in this worksheet development are relevant to SDG 4, particularly in ​​energy conservation. In the context of science education, SDG 4 implementation aims to strengthen student learning outcomes through innovative learning approaches.